Perceptions of the Intensity of Heart Failure Medications among Hospitalized Older Adults: A Pilot Qualitative Study - Nuzha A. Amjad; Saeed Shoar; Catherine Bryant; Meghan Hunt; Min Ji Kwak (Annals of Geriatric Medicine and Research, 2025)
Background Guidelines for heart failure (HF) management recommend high target doses for medications. These targets are based on standardized dosing regimens that rarely consider the complex challenges faced by older patients. However, little is known about such challenges perceived by older adults. We assessed older adults’ perceived challenges with HF medication utilization, which may guide a more patient-centered definition of the target intensity for HF medications. Methods We conducted a pilot qualitative study using one-on-one, semi-structured interviews with older adults. We included patients over the age of 65 years admitted to the acute cardiac care units (cardiac intensive care unit or cardiac intermediate care unit) with a known diagnosis of HF. We conducted a deductive and inductive thematic analysis based on a prior conceptual framework for the Medication-Related Burden Quality of Life tool. Subthemes and themes were finalized with two other coders who were study investigators. Results Ten patients were enrolled in the study. Six major themes were identified in the perception of challenges of HF medication utilization. The most common themes were experiencing adverse drug effects (80%) and psychological distress (80%), followed by problems in logistics (70%), the burden from the number of medications (70%), impact from patient-doctor relations (70%), and burden from the cost (40%). Conclusions The results from this pilot study provide preliminary insight into the perceived challenges of HF medication utilization and the distinctive ways the treatment burden is experienced by patients. These results will need validation in larger studies and different patient settings.